Doctor’s Consultation Fees and Patient’s Willingness to Pay for Doctor’s Consultation Fees in Bangalore, India - Thapa, Radha (Digital Repository of Theses, 2025)
Background: Doctors’ consultation is a doorway to healthcare, and this doorway should be open and accessible to all, which is a basic, uncompromised necessity. But currently, due to disorganized and unsystematic way of charging consultation fees by healthcare providers without considering the willingness to pay for doctors’ consultation, the doorway to healthcare, i.e., doctors’ consultation, has become inaccessible, exposing most of the population to risk. Thus, there was an insurmountable need to establish an approximate range for doctor's consultation fees considering the patients willingness to pay. Objectives: To analyze doctors’ consultation in each specialty of different hospitals, nursing homes and clinics. To measure and investigate the factors influencing patient’s willingness to pay for doctors’ consultation fees and, to recommend appropriate suggestions to frame a better healthcare policy. Methodology: A cross-sectional study was carried out on 2300 doctors’ working in various hospitals, nursing homes and clinics over a period of 10 months in rural and urban areas of Bangalore, India. An Observational checklist was used to analyze the exact range of doctors’ consultation fees being charged. 385 patients were also included in the study to measure the actual willingness to pay towards doctors’ consultation, where each patient was interviewed with a structured questionnaire. The data was tabulated, analyzed, and results were interpreted. Accordingly, recommendations were provided. Results: The current study revealed that, consultation fees charged by General Practitioner was (Rs 885.65), Specialist (Rs 1207.91) and Sub-specialist (Rs 1190.04). Strikingly, On the other hand, the patients were willing to pay in the range of (Rs 251 to 500) for General practitioner, Specialist (Rs 501 to 750), Sub-specialist (Rs 751 to 1000), Additionally, highest average consultation fees were charged by Psychiatrists, followed by Gynecologists, and least was charged by General practitioners. Conclusion: A stark contrast noted in the existing doctors’ consultation and the actual WTP by patients in the same area. Factors influencing patients’ WTP towards doctor consultation fees were observed to be income, household size, disease, area of residence, age of the doctor etc. The conclusive data can be used as an informatic tool by healthcare policymakers, hospitals, and health economist.